THE ROLE OF ISLAMIC MOTIVATION IN MEDIATING EFFECT OF ENTREPRENEURSHIP EDUCATION TO ENTREPRENEURSHIP INTENTIONS DURING THE COVID 19 PANDEMIC - Rizki Febriani; Tri Wahyu Oktavendi (STAI Ma'had Aly Al-Hikam Malang, 2022)
This study aims to determine the relationship between entrepreneurship education on entrepreneurship intention, then between entrepreneurship education on Islamic motivation, the effect of Islamic motivation on entrepreneurship intention and the indirect effect between entrepreneurship education on entrepreneurship intention through Islamic motivation. The sample of this study were students from universities with Islamic values as many as 121 respondents spread across Indonesia. Sampling by purposive sampling method. The results of this study are first, there is an influence between entrepreneurship education on entrepreneurship intention, second, there is a relationship between entrepreneurship education and Islamic motivation, third, Islamic motivation has an effect on entrepreneurship intention and fourth, Islamic motivation is not able to mediate the relationship between entrepreneurship education and entrepreneurship intention. The advice given especially to universities is to provide a forum for students to be able to start their business early on and increase the portion for entrepreneurial practice (not only theory) for students to further hone their skills in business.